1997
DOI: 10.1111/j.1432-1033.1997.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

The Solution Structure and Activity of Caerin 1.1, an Antimicrobial Peptide from the Australian Green Tree Frog, Litoria Splendida

Abstract: Caerin 1.1 is one of the major antimicrobial peptides isolated from the skin of the Australian green tree frog, Litoria splendida. Two‐dimensional 1H‐1H and 1H‐13C NMR spectroscopy in trifluoroethanol/ H2O (50:50, by vol.) have been used to assign the 1H and 13C‐NMR spectra of this 25‐amino‐acid peptide. From an examination of these data, and using distance geometry and molecular dynamics calculations, the solution conformation of caerin 1.1 has been determined. The peptide adopts two well‐defined helices from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
151
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(166 citation statements)
references
References 46 publications
15
151
0
Order By: Relevance
“…78,80,81 For the 25-residue peptide caerin 1.1, the solution conformation has been determined using distance geometry and molecular dynamics calculations. 82 The structural and activity data suggest an interaction with membranes via a carpet-like mechanism. 24 Two other families of antimicrobial peptides have been isolated from L. infrafrenata and L. genimaculata, and were termed frenatins and maculatins, respectively.…”
Section: Peptides From Australian Frogsmentioning
confidence: 97%
“…78,80,81 For the 25-residue peptide caerin 1.1, the solution conformation has been determined using distance geometry and molecular dynamics calculations. 82 The structural and activity data suggest an interaction with membranes via a carpet-like mechanism. 24 Two other families of antimicrobial peptides have been isolated from L. infrafrenata and L. genimaculata, and were termed frenatins and maculatins, respectively.…”
Section: Peptides From Australian Frogsmentioning
confidence: 97%
“…A number of secondary structures of antimicrobial peptides, broadly representative of the above structural groups, have been determined by two-dimensional nmr, either in solution or in model membrane environments. They include cecropins, 89 -92 magainins, [93][94][95] PGLa, 96 sarcotoxin, 97 buforin, 98 caerin, 99 bactenecins, 100 enkelytin, 101 histatin, 102 ranalexin, 103 thanatin, 104 protegrin, 105 tachyplesin, 106 different types of defensins, [107][108][109][110][111][112][113][114][115] and drosomycin.…”
Section: Structural Aspectsmentioning
confidence: 99%
“…The "helix-hinge-helix" structure of caerin 1.1 (GLLSVLGSVAKHVLPHVVPVIAEHL-NH 2 ), determined by 2D NMR in aqueous d 3 -trifluoroethanol as solvent. [3,4] T. Wang et al 03 suite of program [39] at the HF/6-31G* + 5D level of theory by using an iterative least-squares method, see Supporting Information). The restrained electrostatic potential (RESP) charge method developed by Kollman [40] was used for atomic charges, which were then fitted using the RED program.…”
Section: Methodsmentioning
confidence: 99%
“…[1,2] Nuclear magnetic resonance (NMR) studies show that the caerins 1 are hinged peptides when attached to a membrane bilayer. [3,4] Figure 1 shows the three-dimensional (3D) structure of the helix-hinge-helix amphipathic peptide caerin 1.1 and it is suggested that caerin 1.1 interacts with the lipid bilayer of bacterial cells as shown in Fig. 2, [1,2] with the central hinge allowing for insertion of the terminal helix into the membrane, disrupting membrane integrity.…”
mentioning
confidence: 99%